Meningococcal Encephalitis associated with cerebellar tonsillar herniation and acute cervicomedullary injury. (August 2013) - Fayeye, O.; Pettorini, B. L.; Smith, M.; Williams, H.; Rodrigues, D.; Kay, A.
Abstract: A 13-year-old girl presented with a progressive ascending paralysis, bulbar dysfunction and finally respiratory arrest. Magnetic resonance (MR) showed acute cervicomedullary injury and hindbrain herniation. An emergency foramen magnum decompression and external ventricular drainage insertion were performed, and meningococcal infection was diagnosed. The patient recovered completely. Meningococcal encephalitis may have an atypical presentation, and a surgery can optimise the outcome.